2020
DOI: 10.1186/s41100-019-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Falls in systolic blood pressure during dialysis which require no nursing intervention are associated with increased patient intra-dialytic symptom self-reporting and prolonged post-dialysis recovery times

Abstract: Background: Haemodialysis (HD) patients may suffer symptoms during dialysis and take time to recover post HD. We wished to determine whether patients with symptomatic intra-dialytic hypotension (IDH), requiring nursing interventions, or an asymptomatic fall in systolic blood pressure (SBP) reported more symptoms during dialysis. Methods: Six hundred three HD patients completed self-reported intra-dialytic symptom questionnaires and recovery using a visual analogue scale, which were compared with their dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(72 reference statements)
1
4
1
Order By: Relevance
“…This group had similar percentage weight loss and ultrafiltration rates compared to the other groups yet dialysed using a higher dialysate sodium and a lower gradient between the serum and dialysate sodium. Previous studies have suggested that using a higher dialysate sodium and a lower serum to dialysate gradient reduces patient symptoms [34], but our study does not support these earlier reports. However, as we used cooled dialysates, then this may have reduced any potential effect of dialysate sodium.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This group had similar percentage weight loss and ultrafiltration rates compared to the other groups yet dialysed using a higher dialysate sodium and a lower gradient between the serum and dialysate sodium. Previous studies have suggested that using a higher dialysate sodium and a lower serum to dialysate gradient reduces patient symptoms [34], but our study does not support these earlier reports. However, as we used cooled dialysates, then this may have reduced any potential effect of dialysate sodium.…”
Section: Discussioncontrasting
confidence: 99%
“…However, neither total dialysis symptom score nor any individual symptom score was greater in those patients with the greatest fall in aECW, and similarly, there was no effect on post-dialysis recovery time, and this is supported by a recent retrospective analysis [30]. Although one would expect that a fall in systolic blood pressure during dialysis would be associated with more intra-dialytic symptoms, studies have observed that patients starting dialysis with higher blood pressures and with more volume to be removed reported fewer symptoms [30,34]. This may reflect that although blood pressure fell, those who were symptomatic started dialysis with lower blood pressures, so the effect of a subsequent reduction led to greater symptom reporting.…”
Section: Symptommentioning
confidence: 88%
“…In the current work, we found no association between the pre-HD MAP and the DRT; however, we found a negative correlation between the post-HD MAP and the change in the MAP on one hand and the DRT on the other. Similar findings were reported by Yoowannakul et al [ 45 ]. The drop in the blood pressure during HD leads to a reduction in the blood supply to the vital organs like the heart, brain, and mesenteries, which might explain the increase in the number of reports of backache with HD, in addition to the increased frequency of headache, dizziness, breathlessness, and cramps.…”
Section: Discussionsupporting
confidence: 92%
“…Both symptomatic and asymptomatic IDH is associated with significant dialysis patient morbidity both in the short and long term, 55,56 and increased risk of mortality 4 . In the short term, choosing a dialysate with a higher sodium, magnesium, and calcium concentration and lower temperature reduces the risk of IDH.…”
Section: Resultsmentioning
confidence: 99%